2007
DOI: 10.4141/cjas07041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genotype on metabolic variables, colostrum and milk composition of primiparous sows

Abstract: Farmer, C., Charagu, P. and Palin, M. F. 2007. Influence of genotype on metabolic variables, colostrum and milk composition of primiparous sows. Can. J. Anim. Sci. 87: 511-515. Composition of colostrum and milk in first-parity sows from four genetic lines, namely, synthetic Belgian Landrace/Pietrain (B), Duroc (D), Landrace (L) and Yorkshire (Y) were determined. Circulating concentrations of leptin, IGF-I, glucose and FFA were also measured in sows. Differences in colostrum and milk composition were observed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
4
21
1
1
Order By: Relevance
“…Our study was performed in PIC sows of which colostrum composition was not described before. Farmer et al (2007) showed that chemical colostrum composition differs between genotypes yet never as much as we observed. Sows in our study were mostly catabolic during the month before farrowing and we should consider this as a factor affecting colostrum composition.…”
Section: Discussionsupporting
confidence: 53%
“…Our study was performed in PIC sows of which colostrum composition was not described before. Farmer et al (2007) showed that chemical colostrum composition differs between genotypes yet never as much as we observed. Sows in our study were mostly catabolic during the month before farrowing and we should consider this as a factor affecting colostrum composition.…”
Section: Discussionsupporting
confidence: 53%
“…Lactating sows from a Chinese-derived breed, known for its high milking capacity, had more parenchymal RNA and a greater RNA:DNA ratio than Yorkshire sows, whereas mammary DNA was similar for both breeds (Farmer et al 2003). These findings differ somewhat from the present results, where not only RNA, but also mammary cell number was related to milk yield in sows from the same breed.…”
Section: Discussioncontrasting
confidence: 57%
“…Much of the difference in milk production between beef and dairy cows is due to increased mammary Abbreviations: FFA, free fatty acids; GAPDH, glyceraldehyde-3-phosphate dehydrogenase; LEP, leptin; PCR, polymerase chain reaction; PPIA, peptidylpropyl isomerase A; pPRL, porcine prolactin; pPRLR-LF, porcine prolactin receptor, long form; pPRLR-ECD, porcine prolactin receptor extracellular domain, all forms; RG, reference gene; STAT, signal transducers and activators of transcription; WAP, whey acidic protein function, both in terms of the number and secretory capacity of epithelial cells (Keys et al 1989). Differences in the metabolic activity of mammary epithelial cells (RNA:DNA ratio) at the end of lactation were also reported between sows of a traditional white breed and of a Chinese-derived breed with high milking capacity (Farmer et al 2003). A correlation between weight gain of individual piglets and weight and DNA content of the teat nursed by that piglet was reported in sows of traditional white breeds (Kim et al 2000;Nielsen et al 2001).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This could explain why the composition differs between herds (% lactose). Moreover, Farmer et al (2007) showed that chemical colostrum composition differs among genotypes, but we had the same genetic line in different herds. During the first 6 h, IgG alone accounts for most of the total protein (Klobasa and Butler, 1987).…”
Section: Discussionmentioning
confidence: 99%